(3OaY GdTc hGdejf aj JMQjQ Gdafjjf aj Yed GdRLjd hGdehGdjGs
(3ChdgG (B:s
(3CeG HYO aEf GdRLd deG MdG dMfg Ydi cd eYQH hUGQ MaXg Edi GdCagGe COfj hCbQH s
(3BNQgG (B:s
(3eKd gPG GdeWdY EPG cGf GdhRf YdjceG eKd hRfg hgh gPG Je gPG GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3COH JjehQ (B325) s
Keywords: (3GdYQhV hGdbhGais